Strategi Komunikasi Politik Perempuan di Lembaga Legislatif - Zaenal Mukarom (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2011)
The involvement of women role in legislative institution can be said so minim. This condition caused by several factors: (1) culture of national politics communication nuance patrimonial, (2) domestics roles as regulating of family in home, care, parenting and education to child and moral fortress. As a effort to improve women role in politics needed strategy steps done by women them selves throught counter of political communication and strategy tergetted by political party as: prepare generation from women and to be meanstream to women in society